MEWUJUDKAN KOTA RESPONSIF MELALUI SMART CITY - Insani, Priskadini April (Publisia: Jurnal Ilmu Administrasi Publik, 2017)
Realizing Responsive City Through Smart City. Currently, the population growth is very fast, causing various problems especially in the city. The need for accessible, fast, appropriate and accurate information becomes the basic development of information technology in government. The creation of a smart city concept aims to give easiness for the community to overcome all the problems that occur. DOI:Â https://doi.org/10.26905/pjiap.v2i1.1423